Adenotonsillectomy for the treatment of obstructive sleep apnoea in extreme paediatric obesity. Issue 11 (1st November 2022) - Vakharia, N; Murkin, C; Hall, A; Bajaj, Y
Abstract: Objective: Adenotonsillectomy is a recognised treatment for paediatric obstructive sleep apnoea. Recent literature highlights the need to assess outcomes in the extremely obese subpopulation. This study reviewed the efficacy of adenotonsillectomy performed in patients with extreme obesity. Method: A retrospective analysis of attendees at a tertiary paediatric obesity clinic was performed, identifying patients with a body mass index z -score equal to or more than three who had undergone adenotonsillectomy for obstructive sleep apnoea. Electronic patient records, including respiratory polygraphy, were analysed. Results: Nine patients met the study criteria. All required nocturnal non-invasive ventilation pre-operatively. Mean age at referral was 6.9 years, and average age of non-invasive ventilation commencement was 7.8 years. Post-operatively, 8 patients (89 per cent) required non-invasive ventilation with evidence of post-operative obstructive sleep apnoea. Conclusion: In extreme obesity, adenotonsillectomy does not prevent the need for non-invasive ventilation. Management of this patient group requires treatment of obesity alongside potential surgical intervention. Poor efficacy in treating obstructive sleep apnoea may influence the decision to proceed with adenotonsillectomy.